Poisoning & drug overdose - Olson, Kent R. (New Jersey : Prentice-Hall International Inc., 1999)
"Designed for speed of use during toxicologic emergencies, this instant-answer guide delivers critical information on the effective diagnosis and treatment of drug-related emergencies and chemical exposures. Enhanced by detailed tables and charts, extensive cross-referencing, and a comprehensive index, the Seventh Edition has been thoroughly updated to reflect newly released drugs and the latest information on existing drugs. Poisoning & Drug Overdose is divided into four sections: Section 1 leads you through initial emergency management, including treatment of coma, hypotension, and other common complications; physical and laboratory diagnosis; and methods of decontamination and enhanced eliminations of poisons. Section II provides detailed information on hundreds of common drugs and poisons. Section III describes the use and side effects of more than 80 antidotes and therapeutic drugs Section IV covers the medical management of chemical spills and occupational chemical exposures, and includes a table of more than 500 industrial chemicals. Poisoning & Drug Overdose, Seventh Edition should be within reach of every medical toxicologist, emergency physician, and poison control staff member"--Publisher's description
Section I: Comprehensive evaluation and treatment --- Section II: Specific poisons and drugs: diagnosis and treatment -- Section III: Therapeutic drugs and antidotes --- Section IV: Environmental and occupational toxicology.
Includes bibliographical references.
Keywords: POISONING